PEMAHAMAN DAN PRAKTIK HAM PADA SISWA SMA NEGERI 8 SELUMA - Deko Rio Putra; Mirah Lestari; Klora (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines students’ understanding and practice of Human Rights (HR) at SMA Negeri 8 Seluma as part of strengthening civic education in schools. Human Rights education is essential for developing democratic and responsible citizens; however, discrepancies often exist between conceptual knowledge and real-life behavior among adolescents. This research aims to describe students’ level of understanding of fundamental HR principles and analyze how these values are practiced in daily school life. Using a qualitative descriptive method, data were collected from 12 students selected through purposive sampling, supported by interviews with a Civics teacher. Data were gathered through in-depth interviews, observations of student interactions, and documentation of school regulations and HR literacy activities. The results show that students generally understand basic HR concepts such as freedom of expression, the right to protection, equality, and non-discrimination. Nonetheless, inconsistencies remain in practice, indicated by teasing, verbal bullying, and unequal treatment among peers. Positive practices were found in gender equality and religious tolerance, yet challenges persist, including peer influence, immature communication patterns, and limited experiential-based HR education. The study concludes that HR understanding at the cognitive level is relatively good, but its implementation requires strengthening through school culture, modeling, and character-based activities. The findings contribute to the development of contextual HR education strategies in Indonesian secondary schools.